A Mediating Effect of Organizational Climate on the Relationship Between Human Resource Management (HRM) Practices and Human Resource Outcome in Malaysia’s Public Sector - Rajagopal , Mogana Sundaram A/L; Kemat, Baharu Bin (Journal of Digitainability, Realism & Mastery (DREAM), 2025)
This study explores the mediating role of organizational climate in the relationship between Human Resource Management (HRM) practices and Human Resource outcomes within the context of Malaysia’s public sector. The research highlights the importance of HRM practices, such as recruitment, training, performance management, and employee relations, in shaping HR outcomes, including job satisfaction, employee engagement, and organizational commitment. Through a comprehensive survey of public sector employees, the study identifies how organizational climate – defined as the shared perceptions of the work environment – influences these relationships. Results suggest that organizational climate plays a significant mediating role, enhancing the effectiveness of HRM practices in achieving desirable HR outcomes. The findings emphasize the need for public sector organizations to foster a positive organizational climate to maximize the potential of HRM practices. The paper contributes to the understanding of HRM dynamics in the Malaysian public sector and provides practical insights for HR managers aiming to improve employee outcomes through strategic HRM initiatives.